Genome-wide characterization of WRKY family genes in four araceae species and their expression analysis in Amorphophallus konjac - Shi, Haoliang; Zou, Ying; Yang, Min; Qi, Ying; Gao, Penghua; Zhao, Yongteng; Huang, Feiyan; Liu, Jiani; Zhao, Jianrong; Li, Lifang; Yu, Lei (Frontiers in Plant Science, 2025)
IntroductionThe Araceae family is a large family of angiosperms containing many economically valuable and ecologically important species, such as Amorphophallus, Zantedeschia elliottiana, and Spirodela intermedia. The WRKY family is one of the largest plant-specific transcription factor families and plays a crucial role in plant responses to biotic and abiotic stresses.MethodsIn this study, WRKY family members were identified and characterized in four species—Amorphophallus konjac, Amorphophallus albus, Zantedeschia elliottiana, and Spirodela intermedia—using bioinformatics approaches. Characterization included analyses of physicochemical properties, gene structure, phylogenetic relationships, chromosomal distribution, collinearity, and cis-regulatory elements. Expressions were specifically performed in A. konjac using transcriptomics data to examine AkWRKY expression across various tissues and stages of corm development. These expression profiles were further validated by quantitative real-time PCR (qRT-PCR), including tissue types (leaf, petiole, corm, and root); hormone treatments (abscisic acid (ABA)); jasmonic acid (JA); salicylic acid (SA); biotic stress (infection by Pectobacterium carotovorum subsp. carotovorum (Pcc)), and abiotic stresses (low temperature, drought, and salt).ResultsA total of 79, 57, 59, and 36 WRKY members were identified in A. konjac, A. albus, Z. elliottiana, and S. intermedia, respectively, with the majority predicted to be localized in the nucleus. Most WRKY members contained the conserved heptapeptide WRKYGQK domain within their motifs, and genes within the same subgroup shared similar gene structures and motif distributions. Phylogenetic analysis revealed that most Araceae WRKY members belong to Group II. Collinearity analysis indicated that segmental duplication was the primary driving force for the expansion of the WRKY gene family in these Araceae species (Ka/Ks < 1), suggesting the action of purifying selection. Cis-element analysis revealed that the promoter regions of WRKY genes contain numerous regulatory elements associated with plant growth and development, hormone regulation, stress responses, and light responses. Transcriptome analysis demonstrated that AkWRKYs exhibit tissue-specific expression patterns in leaves, petioles, corms, and roots, with most genes revealing up-regulated expression during developmental stages 2 to 3 of the corm. To elucidate the expression patterns of AkWRKYs under biotic and abiotic stresses, qRT-PCR was used to analyze the expression profiles of 14 AkWRKYs in response to ABA, JA, SA treatments, Pcc infection, as well as low temperature, drought, and salt stress. These 14 AkWRKY members displayed significantly differential expression characteristics under hormone regulation, biotic stress, and abiotic stress, responding to various stress treatments to different degrees over time.ConclusionAmong the 79 identified AkWRKY members, AkWRKY38 and 53 exhibited high expression levels in A. konjac under hormone treatments, biotic stress (Pcc infection), and abiotic stresses (low temperature, drought, and salt stress). This study provided new insights into the roles of WRKYs in A. konjac responses to soft rot disease, low temperature, drought, and salt stress. Additionally, it laid a foundation for breeding stress-resistant A. konjac cultivars.